2009
DOI: 10.1063/1.3204457
|View full text |Cite
|
Sign up to set email alerts
|

In situ fabrication of cobalt-doped SrFe2As2 thin films by using pulsed laser deposition with excimer laser

Abstract: The remarkably high superconducting transition temperature and upper critical field of iron(Fe)-based layered superconductors, despite ferromagnetic material base, open the prospect for superconducting electronics. However, success in superconducting electronics has been limited because of difficulties in fabricating high-quality thin films.We report the growth of high-quality c-axis-oriented cobalt(Co)-doped SrFe 2 As 2 thin films with bulk superconductivity by using an in-situ pulsed laser deposition techniq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 23 publications
1
23
1
Order By: Relevance
“…A and B are the curves of the films fabricated with different amount of potassium of 0.48 g and 0.2 g, respectively. B shows better crystallinity as compared to A, and the full width at half maximum of the (008) peak is 0.5° which is comparable with the iron based superconducting films fabricated by in situ method [11].…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…A and B are the curves of the films fabricated with different amount of potassium of 0.48 g and 0.2 g, respectively. B shows better crystallinity as compared to A, and the full width at half maximum of the (008) peak is 0.5° which is comparable with the iron based superconducting films fabricated by in situ method [11].…”
Section: Resultssupporting
confidence: 60%
“…The method of synthesizing targets is similar to that in our previous works [9], [11]. However, the molar ratio of As is decreased from as we used in previous works, so the compositional molar ratio of Fe powder (99.9%) and As pieces (99.99%) is 2.0 and 2.4, respectively.…”
Section: Methodsmentioning
confidence: 72%
“…[2][3][4][5][6][7][8][9][10] However, difficulties overcoming the poor metal/oxide bond at the interface of many substrates has necessitated the need for significant optimization of the deposition parameters 9,10 as well as the use of various intermediate layers 8 to produce well-textured films. In spite of these efforts, nearly all of these films contain an unintentional amorphous or iron-containing layer at the interface.…”
Section: Coherent Interfacial Bonding On the Feas Tetrahedron In Fe/ mentioning
confidence: 99%
“…In fact, besides having a high H c2 , FBS have also shown high intragrain critical current density J c 1617. Despite the relatively low T c (about 22 K in the bulk form), Co-doped BaFe 2 As 2 (Ba122) has been studied by several groups1819202122 because thin film growth is relatively easy compared to other FBS materials. We previously demonstrated that Ba122 thin films have the impressive capability to accept a high density of secondary phases that act as strong pinning centres2325.…”
mentioning
confidence: 99%